Evaluation of diagnosis and treatment results in children with Graves' disease with emphasis on the pubertal status of patients - (:unkn) unknown (FREUND PUBLISHING HOUSE LTD, 2008)
This retrospective study evaluated the clinical and laboratory characteristics at presentation and treatment results of patients with Graves' disease (GD) with respect to pubertal status. Records of 143 patients (108 F, 35 M) were reviewed in a multicenter study. At diagnosis., 38% of patients were prepubertal. Anti-thyroid drugs (ATD) were used as initial therapy. There was no significant difference in clinical and laboratory characteristics at diagnosis, during treatment and adverse reaction to ATD with respect to pubertal status. Twenty patients (7 prepubertal, 13 pubertal) reached remission on ATD. Surgery was performed in seven and radioiodine (RAI) in four patients. Duration of treatment needed to achieve remission was longer in prepubertal (4.2 +/- 1.0 yr) than in pubertal patients (3.1 +/- 1.3 yr) (p = 0.02). The rate of remission was not different between prepubertal (25.9%) and pubertal patients (33.3%) (p = 0.59). ATD were associated with low remission rate in pediatric GD and required longer duration of therapy in prepubertal patients. For definitive treatment in older children, RAI could be evaluated as the initial therapy.
Keywords: Graves' disease; children; pubertal status; remission; anti-thyroid drug therapy; RADIOIODINE TREATMENT; PREPUBERTAL CHILDREN; SURGICAL-TREATMENT; MEDICAL THERAPY; THYROID-CANCER; THYROTOXICOSIS; ADOLESCENTS; HYPERTHYROIDISM; CHILDHOOD; MANAGEMENT